Balance of Payments Pressures on the Exchange Rate - Drahozalová, Anna (2022)
This paper contributes to the existing literature on exchange rate modelling by developing a new proxy for foreign exchange market imbalances. By utilizing the monetary presentation of the Balance of Payments we create a measure of net external monetary flows and study its relationship with the exchange rate. To account for both fixed and floating exchange rate regimes we rely on a version of the exchange market pressure (EMP) index. A structural vector autoregression model provides evidence of a causal relationship from net external monetary flows to the EMP index. We find that a positive orthogonal shock to net external monetary flows causes the exchange rate to appreciate already in the short term with the effect peaking three months after the initial shock.